2016
DOI: 10.1038/cddis.2015.324
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 induces hepatocellular carcinoma EMT and sorafenib resistance by activating FAK/PI3K/AKT signaling

Abstract: Galectin-1 (Gal-1) is involved in several pathological activities associated with tumor progression and chemoresistance, however, the role and molecular mechanism of Gal-1 activity in hepatocellular carcinoma (HCC) epithelial–mesenchymal transition (EMT) and sorafenib resistance remain enigmatic. In the present study, forced Gal-1 expression promoted HCC progression and sorafenib resistance. Gal-1 elevated αvβ3-integrin expression, leading to AKT activation. Moreover, Gal-1 overexpression induced HCC cell EMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
180
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(195 citation statements)
references
References 34 publications
5
180
0
1
Order By: Relevance
“…Once activated, integrins initiate the activation of FAK . It has also been recently reported that the activation of FAK facilitates EMT of HCC cells . In this study, as expected, the phosphorylation of FAK was notably inactivated in Talin1‐knockdown cells, indicating that Talin1‐mediated EMT is FAK‐independent (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Once activated, integrins initiate the activation of FAK . It has also been recently reported that the activation of FAK facilitates EMT of HCC cells . In this study, as expected, the phosphorylation of FAK was notably inactivated in Talin1‐knockdown cells, indicating that Talin1‐mediated EMT is FAK‐independent (Fig.…”
Section: Resultssupporting
confidence: 86%
“…For example, miR‐128 potently reverses metastasis and chemoresistance of highly malignant NSCLC cells, which could be completely reversed by restoring pro‐EMT signaling pathway activities, including Wnt/β‐catenin and TGF‐β (Cai et al, ). In our previous study, we reported that overexpression of galectin‐1 can induce EMT in HCC cells through activating the PI3K/AKT cascade signaling pathway, which can counteract the effect of sorafenib (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of MMP1 22 and LGALS1 23 has been identified to correlate with poor prognosis of CRC patients, and upregulated MMP1 and LGALS1 induce the development of EMT in cancer 24, 25 . Prognostic analysis using CRC cohort from TCGA showed no prognostic significance of MMP1 (see Supplementary Figure S3), whereas our result and another study have confirmed the prognostic significance of MMP1 in CRC patients 22 .…”
Section: Discussionmentioning
confidence: 99%